The hidden force opposing ice compression - Zhang, Xi (2013)
Coulomb repulsion between the unevenly-bound bonding “–” and nonbonding “:” electron pairs in the “O2−:H+/p–O2−” hydrogen bond is shown to originate the anomalies of ice under compression. Consistency between experimental observations, density functional theory and molecular dynamics calculations confirmed that the resultant force of the compression, the repulsion, and the recovery of electron-pair dislocations differentiates ice from other materials in response to pressure. The compression shortens and strengthens the longer-and-softer intermolecular “O2−:H+/p” lone-pair virtual bond; the repulsion pushes the bonding electron pair away from the H+/p and hence elongates and weakens the intramolecular “H+/p–O2−” real bond. The virtual-bond compression and the real-bond elongation symmetrize the “O2−–H+/p:O2−” as observed at 60 GPa and result in the abnormally low compressibility of ice. The virtual-bond stretching phonons (<400 cm−1) are thus stiffened and the real-bond stretching phonons (>3000 cm−1) softened upon compression. The cohesive energy loss of the real bond dominates and lowers the critical temperature for the VIII–VII phase transition. The polarization of the lone electron pairs and the entrapment of the bonding electron pairs by compression expand the band gap consequently. Findings should form striking impact to understanding the physical anomalies of H2O.